Efficacy and safety of sapropterin dihydrochloride in patients with phenylketonuria: A meta‐analysis of randomized controlled trials. Issue 5 (18th March 2019) - Qu, Jinghan; Yang, Ting; Wang, Ente; Li, Min; Chen, Chaoyang; Ma, Lingyun; Zhou, Ying; Cui, Yimin
Abstract : Aims: The aim of the present meta‐analysis was to evaluate the efficacy and safety of sapropterin dihydrochloride in phenylketonuria (PKU) patients. Methods: The following databases were searched for randomized controlled trials (RCT) regarding PKU patients treated with sapropterin dihydrochloride: PubMed, Embase, Cochrane Library and clinicaltrials . Two authors independently selected studies, assessed the risk of bias and extracted data. The meta‐analysis was performed in RevMan 5.3 provided by the Cochrane Collaboration. Results: Four studies met the inclusion criteria. In PKU patients with low blood phenylalanine (Phe) concentration, no significant difference was indicated for the decrease of Phe level (weighted mean difference (WMD) = −7.75 μmol L −1 ; 95% confidence intervals (CI): −82.63 to 67.13, P = 0.84, I 2 = 0%), however, the dietary Phe tolerance was significantly improved in the sapropterin group (WMD = 19.89 mg kg −1 d −1 ; 95% CI: 10.26 to 29.52, P < 0.0001, I 2 = 0%). In PKU patients with high blood Phe level, sapropterin showed a significant lowering in blood Phe concentration (WMD = −225.31 μmol L −1 ; 95% CI: −312.28 to −138.34, P < 0.00001, I 2 = 0%). There was no significant difference for adverse events. Conclusions: Sapropterin could bring benefit for PKU patients with high or low Phe level, due to Phe reduction in a short time or dietary Phe tolerance improvement respectively. Sapropterin has an acceptable safety profile.